Barriers to pre‐emptive kidney transplantation in New Zealand children. (7th May 2021) - Weststrate, Harriet; Ronaldson, Jane; Yonge, Georgina; Dickens, Amanda; Erickson, Robin; Wong, William; Prestidge, Chanel
Abstract : Aim: Pre‐emptive kidney transplantation (PKT) is generally considered the optimal treatment for kidney failure as it minimises dialysis‐associated morbidity and mortality and is associated with improved allograft survival. This study aimed to determine rates of paediatric PKT in New Zealand, identify barriers to PKT and consider potential interventions to influence future rates of pre‐emptive transplantation. Methods: Children commencing kidney replacement therapy between 2005 and 2017 in New Zealand were included. Descriptive analysis considered those referred late (referral <3 months prior to kidney replacement therapy initiation) or early based on referral timing to paediatric nephrology. Additional analysis compared characteristics of children receiving dialysis versus pre‐emptive transplant as their first mode of kidney replacement therapy. Results: PKT occurred in 15 of 90 children (17%). One‐third of all patients were referred late. No late referrals received a pre‐emptive transplant. Pre‐emptively transplanted children were referred younger (median age 0.49 years), lived in less deprived areas, were more likely to have congenital anomalies of the kidney and urinary tract and none were Māori or Pasifika ethnicity. Conclusions: Late referral, higher deprivation levels and Māori and Pasifika ethnicity confer a greater risk of not receiving pre‐emptive transplantation. Improved education amongst health professionals about recognition of paediatric chronic kidney disease and the importance of timely referral to paediatric nephrology is recommended to reduce rates of late referral. A modified approach including enhanced culturally appropriate support for those diagnosed with chronic kidney disease during transplant evaluation should be pursued to improve equity.